The effectiveness of a rational-emotive intervention on teachers’ unconditional self-acceptance, perfectionism, and pupil control ideology - Samfira, Elena Mirela; Sava, Florin Alin (Frontiers in Psychology, 2023)
Introduction The present research aimed to investigate the effectiveness of a Rational Emotive Behavior Therapy (REBT) intervention on in-service teachers. Methods A quasi-experimental 2-group (intervention vs. control) × 3-time (pre, post-test, follow-up) design was applied to explore to what extent the REBT interventions help teachers increase their level of unconditional self-acceptance as the primary outcome and decrease their perfectionism tendencies and pupil control ideology as secondary outcomes. The sample consisted of 100 in-service teachers assigned to either the intervention group (n = 50) or the control group (n = 50). The experimental group received a 6-week intervention program. Every session was held weekly and lasted 90–120 min. The Unconditional Self-Acceptance Questionnaire (USAQ), Pupil Control Ideology Scale (PCI), and Perfectionism Inventory Scale (PI) were used to collect data. This study used a mixed model ANOVA 2 × 3 for data analysis. Results The results indicated that in the experimental group, there was a statistically significant increase in unconditional self-acceptance level from pre-test to post-test, which remains significant at the 6-month follow-up. Likewise, there were no statistically significant differences in unconditional self-acceptance levels between the post-test and 6-month follow-up in the intervention group. Discussion These findings prove that REBT interventions are effective in increasing teachers’ unconditional self-acceptance.